Antimicrobial, anti-adhesive and anti-biofilm potential of biosurfactants isolated from Pediococcus acidilactici and Lactobacillus plantarum against Staphylococcus aureus CMCC26003. (February 2019) - Yan, Xin; Gu, Shanshan; Cui, Xingyang; Shi, Yunjia; Wen, Shanshan; Chen, Hongyan; Ge, Junwei
Abstract: Biosurfactants (BS) are amphipathic compounds produced by diverse groups of microorganisms exhibiting various biological activities. The current study aimed to assess antimicrobial, anti-adhesive and anti-biofilm activities of BS isolated from lactic acid bacteria (LAB), including Pediococcus acidilactici and Lactobacillus plantarum against Staphylococcus aureus CMCC 26003 in vitro. Cell-bound BS from both Pediococcus acidilactici and Lactobacillus plantarum were extracted, and their surface activities were evaluated by oil spreading assay. As quantified by crystal violet method, BS inhibited adhesion and biofilm formation of Staphylococcus aureus in a dose-dependent manner. The above findings were further supported by results of scanning electron microscopy. These two kinds of BS affect expressions of biofilm-related genes ( cidA, icaA, dltB, agrA, sortaseA and sarA ) and interfere with the release of signaling molecules (AI-2) in quorum sensing systems. Biological activities observed for BS produced by tested LAB suggest prospects for their use against Staphylococcus aureus biofilm-related infections. Highlights: Crude BS produced by L. plantarum and P. acidilactici has good anti-adhesion and anti-biofilm activity against S. aureus . The expression of genes related to biofilm formation (cidA, icaA, dltB, agrA, sortaseA and sarA) is affected by crude BS. Crude BS interfere with the release of signaling molecules (AI-2) in quorum sensing systems. BS can be used as special anti-bacterial biofilm biologicals, but has minimal effect on bacterial growth.